(untitled) (Research, Society and Development, 2022)
Bariatric surgery is an option for obese patients who have tried other conventional ways to lose weight without success. However, the postoperative period of these patients is a real challenge, especially in relation to weight regain, due to years of inadequate eating habits and lifestyle. The aim of this study was to evaluate the incidence of weight regain and associated factors in patients undergoing bariatric surgery. A questionnaire was applied online, with questions related to personal issues, as well as questions about the pre- and post-surgical conditions of the patients. 107 volunteers were evaluated, 93.5% (n=100) female and 6 .5% (n = 7) were male, aged between 22 and 58 years and mean age was 39 years. Of this total, 52.3% (n=56) stated that they practice physical activity frequently; 62.6% (n=67) claimed not to have any harmful or addictive habits, 23.4% (n=25) consume alcoholic beverages, 8.4% (n=9) are smokers and 5.2% (n= 6), claim to have both habits. 83.17% (n=89) of the volunteers reported making changes in their eating habits after surgery, but 63.6% (n=68) reported a case of weight regain after surgery. It is concluded that, despite the majority having adhered adequately to a change in eating habits, almost half of those evaluated did not adhere to the practice of physical activities, leading to a very worrying rate of weight regain.